Sistem Informasi Manajemen Inventaris Aset Berbasis Web pada DPMD Sumatera Selatan - Fauzan Aziman Putra; Gusmelia Testiana (INDO PUBLISHING, 2026)
The inventory management process at the Department of Community and Village Empowerment (DPMD) of South Sumatra Province was still carried out semi-manually using spreadsheets and conventional records, resulting in data redundancy, difficulties in asset tracking, and inefficiencies in report preparation. This study aims to design and develop a Web-Based Office Inventory and Asset Management Information System to support centralized and integrated asset management. The system was developed using the Rapid Application Development (RAD) method, which emphasizes iterative development and active user involvement. The application was built using the Laravel framework and MySQL database, providing features such as inventory data management, asset condition monitoring, mutation and borrowing records, and automated report generation. System testing was conducted using the Black Box Testing method to evaluate the functionality of each feature. The results indicate that all system functions operate according to user requirements and successfully support inventory management activities. The implementation of the system improves data accuracy, facilitates asset tracking, accelerates report generation, and enhances operational efficiency in managing office assets at DPMD South Sumatra Province.